2019
DOI: 10.30649/htmj.v16i2.117
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan antara Indeks Massa Tubuh dan Tingkat Kebugaran Jasmani dengan Mengukur Vo2 Maks pada Nelayan Penyelam di Kelurahan Kedung Cowek Surabaya

Abstract: <h1>ABSTRAK</h1><p><strong>Latar Belakang</strong>: Indeks massa tubuh (IMT) adalah teknik yang paling sering digunakan untuk mengukur lemak tubuh. Kebugaran jasmani adalah kemampuan seseorang untuk melakukan aktivitas fisik. Penurunan kebugaran jasmani dan peningkatan lemak tubuh merupakan faktor penting berkembangnya komorbiditas kardiovaskular. Kebugaran jasmani dipengaruhi oleh faktor-faktor seperti genetik, usia,  IMT , aktivitas fisik, dan lain - lain. Peningkatan lemak tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Step Test in 23 diver fishermen was found to be not significant (r = -0.01, p = 0.944). 17 CRF level of 16 normal weight and 16 overweight medical students were significantly different. 21 We assume a difference in sample size could be the reason for discrepancies of findings in these studies from others, which may also be taken into consideration when interpreting the result of the present study since we included a total of 51 subjects.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Step Test in 23 diver fishermen was found to be not significant (r = -0.01, p = 0.944). 17 CRF level of 16 normal weight and 16 overweight medical students were significantly different. 21 We assume a difference in sample size could be the reason for discrepancies of findings in these studies from others, which may also be taken into consideration when interpreting the result of the present study since we included a total of 51 subjects.…”
Section: Discussionmentioning
confidence: 88%
“…Most studies found a negative association between both variables but some studies had different results. [9][10][11][12][13][14][15][16][17][18] The objective of this study is to analyze the association between BMI and CRF that is measured by cardiac stress test.…”
Section: Introductionmentioning
confidence: 99%
“…This study used the Pearson Chi-square correlation test to examine the relationship between Body Mass Index (BMI) and the level of physical fitness of Ministry of Health employees. The analysis findings show that there is no significant correlation between BMI and physical fitness level (p=0.159) [24,25].…”
Section: Discussionmentioning
confidence: 99%